Variability and genetic structure of yellow passion fruit (Passiflora edulis f.flavicarpa Degener) in Colombia using microsatellite DNA markers - Ocampo Pérez, John A.; Acosta-Barón, Natali; Hernández Fernández, Javier (Universidad Nacional de Colombia, 2017)
Colombia is one of the leading producers of yellow passion fruit but the genetic studies based on molecular markers from commercial plantations have not been considered to select interesting market material. The goal of this study was to assess the genetic variability and the population structure of 51 Colombian commercial yellow passion fruit accessions (102 individuals), and to provide the necessary information for prospective selection and breeding programs. Thus, a total of six microsatellites were amplified with 58 alleles identified and an average of 9.66 alleles per locus, including nine private and 31 rare. Diversity indexes showed polymorphic information content values of 0.74 (PIC), an observed (Ho) and expected (He) heterozygosity average of 0.52 and 0.78, respectively. Spatial distribution showed the greatest allelic richness (11 to 14) in most of the Valle del Cauca accessions. The average genetic distance among accessions was 0.68, and the cluster analysis showed three main groups poorly supported (bootstrap <50%), with slight geographical structure and high differentiation between individuals of the same accession. Structure analysis indicated K=4 as the genetic structure´s uppermost hierarchical level, while Bayesian clustering showed a division of individuals into four genetically distinct groups. The low geographic structure and high variability of the accessions could be explained by allogamy and seed exchange frequency among farmers. Results issued suggest a complementary agromorphological assessment to establish total genetic variability and implement a breeding program through assisted selection of superior genotypes in search of more productive and resistant cultivars to phytosanitary problems.